Η επίδραση της επεξεργασίας με υψηλή υδροστατική πίεση στη μικροβιολογική ποιότητα του ζαμπόν και των λουκάνικων Φρανκφούρτης κατά τη διάρκεια ζωής τους - Τάκη, Αναστασία (Τμήμα Γεωπονικών Επιστημών,Βιοτεχνολογίας και Τεχνολογίας Τροφίμων,Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Several factors threaten the shelf-life and freshness of meat products. Among these factors are temperature, oxygen, humidity and presence of microorganisms. High Pressure Processing (HPP) is aiming to replace traditional thermal processing methods, allowing pasteurisation of food near or at room temperatures, enabling them to better maintain flavour, nutritional properties and overall product quality. In this study we have evaluated the efficiency of HPP on commercial ham and Frankfurt sausages. Twenty vacuum packed samples from the same batches of ham and Frankfurt sausages were taken; ten samples of each product were processed with HPP at 6000 bar for three minutes, whilst the remaining ten were not. Both sets of samples were then stored at 4 oC for a period of two months and weekly analysed for the following parameters: Total Aerobic Count (TAC), Coliforms, E. coli, Staphylococci, Yeasts and Moulds, Salmonella spp. and Listeria monocytogenes. At the end of their shelf life the HPP ham had a TAC count of 100 cfu/g whereas the non-HPP had a TAC >1011 cfu/g and the HPP Frankfurt sausages 6,15 x 102 cfu/g with the non-HPP 3,3 x 109 cfu/g demonstrating the significant efficiency of HPP on the shelf-life of both products tested.
Keywords: Meat; Sausages; Κρέας; Λουκάνικα